DINAMIKA KONSEP DIRI PADA ORANG DEWASA KORBAN CHILD ABUSED - Fatimah, Siti Nur (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThe purpose of this research was to determine the dynamics of self-conceptamong early adult who experienced child abused and to study the impact ofself-concept on their behavior in the community. The subject of present studyis 2 adult male and female who have been victims of child abused. Datacollection techniques in this study was conducted using semi-structuredinterviews, non-participant observation and projective tests (BAUM, DAP,HTP). Data analysis was done in this research used content analysis. Thepurpose of content analysis is to describe the dynamics of self-concept amongearly adult who experienced child abused. The approach used in this researchis case study. The results of this research indicated that after receiving a childabused, two subjects had low confidence but after a subject growing up, self-concept is formed on both subjects are positive self-concept. Positive self-concept is formed from available support and motivation from others (friends),the awareness of spirituality such as prayer and always take lessons from whathas happened. The impact of a positive self concept makes better relationshipswith the community and the subject easier to get along with other people.Keywords : self-concept, adult, child abused.